Contextos arqueológicos de los textos ibéricos valencianos (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The Iberian texts found in central areas of Valencia are substantial and extensive, but many of them lack of archaeological contexts. Recent research in the territory around the city of Edeta/Llíria and in the oppidum of Bastida de les Alcusses prove that contextualization of epigraphic findings is transcendental for their dating. Among the reasons for this are the elucidation of present day divergent opinions about the different Iberians alphabets origin and, above all, the understanding of the social use and meaning of these documents.
Keywords: Epigraphy; Iberian Texts; Figurative Pottery; Lead Tablets; Archaeological Context